'In the liveliest place, my mother's bosom, there was death' – mother-daughter relationships in the work of Rachel Nemesh, Second-Generation Holocaust survivor. Issue 1 (2nd January 2022) - Marnin-Distelfeld, Shahar
ABSTRACT: This article focuses on the artwork of Israeli artist, Rachel Nemesh, a Second-Generation Holocaust Survivor. The assemblage to be discussed was exhibited in her solo exhibition, One Flesh, in 2020. The corpus analysis will be divided into four themes: (a) The Big Mother – works describing the elderly mother of Nemesh in a monumental manner; (b) Pieta versions – works focusing on bodily scenes of mother and daughter closely tangled; (c) Body-Parts: works showing randomly detached body organs; (d) Domestic Space – the artist's mother in her home. The study will be framed by two main fields: art centering on the Holocaust and feminist ideas focusing on mother-daughter relationships. Theoretical and visual examination will be enhanced by interviews with the artist aiming at profoundly decoding her artwork, claimed to resonate a feminine artistic language. An attempt to formulate an original interpretation of Holocaust Second-Generation's art, combined with a feminist point of view, will be made here. Rachel Nemesh's artwork is being investigated here for the very first time.